Relationship between Helicobacter pylori Infection and Chronic Obstructive Pulmonary Disease - Seyyed Hamid Hashemi; Ebrahim Nadi; Mehrdad Hajilooi; Mohammad-Ali Seif-Rabiei; Uldoz Roustaei (Acta Medica Iranica, 2011)
There is some evidence indicating the role of Helicobacter pylori infection in pathogenesis of extragastrointestinal diseases including skin, vascular, and autoimmune disorders, as well as some respiratory diseases. The aim of this study was to investigate the association between H. pylori and chronic obstructive pulmonary disease (COPD). In a case-control study, 90 patients with COPD and 90 age- and sex- matched control subjects were included. Serum samples were tested for anti-H. pylori and anti-CagA IgG by ELISA. A physician completed a questionnaire including demographic characteristics, habitual history, and spirometric findings for each patient. Of 90 patients with COPD 66 (51%) had mild, 31 (34.4%) moderate, and 13 (14.4%) sever disease. There was no significant association between H. pylori IgG seropositivity and COPD. Serum levels of anti-CagA IgG were significantly higher in patients with COPD than in the control subjects (P < 0.001). No association was observed between H. pylori infection and severity of COPD. The results suggest that there is an association between CagA-positive H. pylori infections and COPD. Further studies should be planned to investigate the potential pathogenic mechanisms that might underlie these associations.